HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG INFEKSI NOSOKOMIAL DENGAN KEPATUHAN MENCUCI TANGAN DI RSU KABUPATEN TANGERANG 2017 - Yunita Ahda (STIKes IMC Bintaro, 2017)
Nosocomial infection is very important to be known by medical personnel, especially nurses because nurses are more often in direct contact with patients, washing hands is one effort to prevent nosocomial infections. Knowing the relationship of nurse knowledge level about nosocomial infection with handwashing compliance at Tangerang District Hospital. The method to be used is by using descriptive correlation study method (Correlation Study).], And handwashing observation. The population in this study were nurses at Tangerang District Hospital in 2017. Data analysis for univariate using bivarian sequence analysis frequency using chi square. Most of the male sex of 15 people or approximately (30.0%). Aged 20 years - 30 years as many as 32 respondents or about 64.0%. Educated D3 Nursing with as many as 34 respondents or about 68.0%. Length of work 1 year - 5 years as many as 29 or about (58.0%). Non-pns as many as 43 or about (86.0%). Married status of 39 or about (78.0%). Knowledge of nosocomial infection is good as 26 (52.0%) and behavior less 0 (0.0%), while nurse with compliance less 2 (4.0%) and less behavior as much as 24 (48.0%). Nurses are advised to do handwashing compliance in 5 moments.